The Role Of Fintech In Sharia Rural Bank West Sumatra - Nasfi, Nasfi; Yunimar, Yunimar; Prawira , Adi (IJOSMAS, 2022)
The writing of this article is sourced from the Research Library Research, the purpose of this study is to see how much influence fintech has on the operational development of Islamic Rural Banks in an area, with the research area of ​​West Sumatra, with descriptive qualitative research methods with secondary data sources. At this time the development of technology is so rapid, which has spread to the financial sector, both banking and non-banking, with a new era called financial technology (Fintech). Fintech is a financial service provider that brings together givers and recipients in order to enter into loan agreements in rupiah currency directly through an electronic system. Fintech will be a medium that strengthens the economy in Indonesia if it is managed properly. Sharia Rural Banks must develop or adjust operations following the development of technology (fintech), which is increasingly reaching areas that are impossible to account for in banking calculation products. This research is expected to contribute knowledge about fintech that affects every operational activity in banking, and can also be an evaluation related to how important fintech is in financial institutions including sharial rural banks.